2008
DOI: 10.1111/j.1530-0277.2008.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Children With Heavy Prenatal Alcohol Exposure Demonstrate Deficits on Multiple Measures of Concept Formation

Abstract: Deficits in concept formation and conceptual set shifting were observed in alcohol-exposed children with or without the diagnosis of FAS and in the absence of mental retardation. These deficits likely impact problem solving skills and adaptive functioning and have implications for therapeutic interventions in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
2
28
0
2
Order By: Relevance
“…Overall, the articles that assessed intellectual functioning in individuals prenatally exposed to alcohol found general impairment in intelligence. 13,15,16,20,[25][26][27][28][29][30][31][32][33][34]45 This fi nding was consistent with the revisions included in this study. 11,12,22,32,38,39 Curiously, while compiling the studies data, we found that the intellectual performance injury occurs diff erently depending on the individual diagnosis.…”
Section: General Intelligencesupporting
confidence: 78%
“…Overall, the articles that assessed intellectual functioning in individuals prenatally exposed to alcohol found general impairment in intelligence. 13,15,16,20,[25][26][27][28][29][30][31][32][33][34]45 This fi nding was consistent with the revisions included in this study. 11,12,22,32,38,39 Curiously, while compiling the studies data, we found that the intellectual performance injury occurs diff erently depending on the individual diagnosis.…”
Section: General Intelligencesupporting
confidence: 78%
“…Not surprisingly, impairments in executive control are associated with reduced quality of life due to negative impact on employment, managing finances and personal relationships (Royall et al, 2002). The specific impairment seen in the current study is particularly intriguing given evidence from the clinical literature that executive control is impaired in individuals with Fetal Alcohol Syndrome (McGee et al, 2008). Further, executive functioning has been shown to predict level of social skill, suggesting that alterations in these domains may underlie a wide range of deficits after PAE (Schonfeld et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…There is considerable support for the relation between FASD and weaknesses in the three EF components in Miyake's model: working memory (e.g., Malisza et al 2012;O'Hare et al 2009), inhibition (e.g., Fryer et al 2007;Mattson et al 1999) and set-shifting (e.g., Kodituwakku et al 2001b;McGee et al 2008). Despite numerous studies demonstrating a significant relation between FASD and widespread EF deficits, considerable variability has been found in terms of types of EF assessed, methodology and findings (Rasmussen 2005).…”
mentioning
confidence: 95%